Manufacturing process of LED color-changing laminated glass
By adopting the production process of LED color-changing laminated glass in the production process of cavity glass, the problems of complex preparation process and difficult detection in the prior art are solved, efficient preparation and quality inspection are achieved, and production efficiency and product pass rate are improved.
Patent Information
- Application Number
- CN202411812326.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art When preparing cavity glass, the process is complicated and the quality of the finished product cannot be effectively detected, which affects the production efficiency and product qualification rate.
The production process of LED color-changing laminated glass is adopted. By setting the electrode layer and color-changing layer on the lower and upper glass substrates respectively, integrating it through vacuum pressing, then adding film and hot pressing, the finished product is finally tested for beam intensity and color strength.
The glass preparation process is simplified and the production efficiency is improved. The finished product can be prepared directly without considering the shape of the glass substrate, and the product quality is ensured through inspection, which improves the batch pass rate.
Smart Images

Figure CN119704851A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of color-changing glass, and in particular relates to a manufacturing process of LED color-changing laminated glass. Background Art
[0002] With the continuous development of my country's economy and the improvement of people's living standards, consumers pay more and more attention to the environmental protection of various building materials and have higher and higher requirements for aesthetics. Glass is a commonly used building material.
[0003] In the production process of glass, in order to improve the thermal insulation performance, cavity glass is often used. Cavity glass is two or more pieces of glass separated by an effective sealing layer. A certain method is used to form a dry cavity between the glass and the glass. The cavity is vacuum and is not filled with any gas. In this way, the heat transfer of air through conduction, convection and radiation between the glass is effectively prevented. Under the influence of outdoor temperature, the deformation of the glass is basically zero when it is transmitted to the middle. Therefore, the use of double-layer glass can save energy.
[0004] However, during the preparation process, the shapes and sizes of the glass vary. Therefore, when the glass is pressed, different layers need to be sheared. Therefore, the preparation method is relatively complicated. Secondly, it is impossible to form an effective detection method for the finished product. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a process for manufacturing LED color-changing laminated glass.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions, including:
[0009] Making a lower-layer coated glass body;
[0010] Making an upper coated glass body;
[0011] A film is added between the lower coated glass body and the upper coated glass body, and a finished product is obtained through lamination.
[0012] As a preferred solution of the manufacturing process of the LED color-changing laminated glass of the present invention, the manufacturing steps of the lower coated glass body include:
[0013] A lower electrode layer is disposed on the upper surface of the lower glass substrate;
[0014] A first color-changing layer is disposed on the upper surface of the lower electrode layer;
[0015] The lower glass substrate, the lower electrode layer and the first color-changing layer are integrated into a whole by vacuum pressurization to obtain a lower coated glass body.
[0016] As a preferred solution of the manufacturing process of the LED color-changing laminated glass of the present invention, the manufacturing steps of the upper coated glass body include:
[0017] An upper electrode layer is disposed on the lower surface of the upper glass substrate;
[0018] A second color-changing layer is disposed on the lower surface of the upper electrode layer;
[0019] The upper glass substrate, the upper electrode layer and the second color-changing layer are integrated into a whole by vacuum pressurization to obtain an upper coated glass body.
[0020] As a preferred solution of the manufacturing process of the LED color-changing laminated glass of the present invention, the manufacturing steps of the upper coated glass body include:
[0021] An upper electrode layer is disposed on the lower surface of the upper glass substrate;
[0022] The upper glass substrate and the upper electrode layer are integrated into a whole through vacuum pressurization to obtain an upper coated glass body.
[0023] As a preferred solution of the manufacturing process of the LED color-changing laminated glass of the present invention, the preparation step of the lower coated glass body further includes:
[0024] Use a heating plate to heat the lower glass substrate, and set the temperature to 175-185°C;
[0025] Then evaporate the lower electrode layer onto the lower glass substrate, and then perform secondary heating by an infrared heat lamp, the temperature is set to 200-600°C, and the pressure is set to 4mTorr by using a vacuum device, and argon is used for secondary electric field acceleration, the flow rate of argon is set to 100-200sccm, the electric field voltage is set to 800-1000V, and during the second pressurization, turn off the infrared heat lamp, set the secondary pressurization time to 2min, and then fill the pressure in the vacuum device to 1mTorr to obtain the prepared part;
[0026] Heat the color-changing ink to 60-90°C and spray it on the workpiece by electrostatic spraying. The thickness of the color-changing ink spraying is 0.007-0.03mm. Then, nitrogen is introduced to blow away the excess powder. The volume flow rate of the introduced nitrogen is 0.2m3 -5m 3 / h, and finally the lower layer of coated glass is obtained by hot air drying.
[0027] As a preferred solution of the manufacturing process of the LED color-changing laminated glass of the present invention, wherein: when the upper electrode layer and the upper glass substrate are integrated into a whole;
[0028] Use a heating plate to heat the upper glass substrate, and set the temperature to 165-175°C;
[0029] The upper electrode layer is then evaporated onto the upper glass substrate, and then heated for a second time by an infrared heat lamp, the temperature is set to 200-550°C, and the pressure is set to 3-4mTorr using a vacuum device. Argon is used for secondary electric field acceleration, the argon flow rate is set to 100-200sccm, the electric field voltage is set to 800-950V, and during the second pressurization, the infrared heat lamp is turned off, the second pressurization time is set to 1-2min, and the pressure in the vacuum device is filled to 1mTorr to obtain an upper coated glass body.
[0030] As a preferred solution of the manufacturing process of the LED color-changing laminated glass of the present invention, when preparing the finished product, the specific steps include:
[0031] Add a film between the lower coated glass body and the upper coated glass body, put them into a vacuum bag, and evacuate them at a vacuum degree of 2.5 kPa for 10-15 minutes to obtain a pre-pressed product;
[0032] Then put the pre-pressed product into the autoclave, set the pressure to 1.3MPa, the duration to 20-30min, the temperature to 100-135℃, and obtain the hot-pressed product;
[0033] The hot pressed product is then stored at a temperature of 70-100°C for 2 hours, then taken out and allowed to stand to cool, and then cut to size to obtain the finished product.
[0034] As a preferred solution of the manufacturing process of the LED color-changing laminated glass of the present invention, after obtaining the finished product, the quality of the finished product is tested, wherein the testing step includes:
[0035] Before the finished product changes color: a light beam is emitted through the finished product, and the intensity is detected by a light beam detector at the other end of the finished product to obtain a first detection value;
[0036] After the finished product changes color: a light beam is emitted through the finished product, and the intensity is detected by a light beam detector at the other end of the finished product to obtain a second detection value;
[0037] Analyze the first detection value and the second detection value to obtain a beam intensity score;
[0038] The steps to test the quality of finished products also include:
[0039] Before the finished product changes color: set a color block image on one side of the finished product, and shoot with a camera on the other side of the finished product to obtain a first test image;
[0040] After the finished product changes color: set a color block image on one side of the finished product, and shoot with a camera on the other side of the finished product to obtain a second test image;
[0041] Analyze the first test image and the second test image to obtain color strength scores;
[0042] The beam intensity score and the color intensity score are combined to output a final score for the finished product. When the final score is greater than the threshold, the finished product is qualified.
[0043] As a preferred solution for the manufacturing process of the LED color-changing laminated glass of the present invention, the calculation formula of the beam intensity score is:
[0044]
[0045] Wherein, G represents the beam intensity score, I1 and I2 represent the first detection value and the second detection value respectively, and α represents the determination factor, which is specifically 1 or 0;
[0046] The calculation formula of the color strength score is:
[0047]
[0048] In the formula, Y represents the color intensity score, U1 and U2 represent the first analysis value and the second analysis value respectively, and β represents the determination factor, which is specifically 1 or 0.
[0049] As a preferred solution for the manufacturing process of the LED color-changing laminated glass of the present invention, the calculation formula of the final score is:
[0050]
[0051] In the formula, Z represents the final score.
[0052] Beneficial effects of the present invention:
[0053] First, the lower glass substrate, the lower electrode layer and the first color-changing layer are pressed into a whole, and then the lower coated glass body and the upper coated glass body are obtained respectively in the same way, and then the finished product is made. The prepared finished product is cut according to actual needs. Compared with the existing method, this method does not need to consider the shapes of the lower glass substrate and the upper glass substrate, and can be directly prepared, which greatly improves the preparation efficiency.
[0054] After preparation is completed, through the inspection of the finished products, substandard products can be eliminated to ensure the pass rate of the entire batch. Secondly, the combination of the two sets of testing standards improves the testing efficiency, and they can form judgments with each other to ensure the authenticity of the test. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:
[0056] Figure 1 This is the first structural diagram of LED color-changing laminated glass.
[0057] Figure 2 This is the second structural diagram of LED color-changing laminated glass. DETAILED DESCRIPTION
[0058] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0059] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0060] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0061] The raw materials used in the present invention are all commercially available unless otherwise specified.
[0062] Example 1
[0063] This embodiment provides a method for preparing a lower coated glass body (100) and an upper coated glass body (200), referring to Figure 1 , specifically:
[0064] The manufacturing steps of the lower coated glass body 100 include:
[0065] A lower electrode layer 102 is disposed on the upper surface of the lower glass substrate 101;
[0066] A first color-changing layer 103 is disposed on the upper surface of the lower electrode layer 102;
[0067] The lower glass substrate 101 , the lower electrode layer 102 and the first color-changing layer 103 are integrated into a whole by vacuum pressurization to obtain a lower coated glass body 100 .
[0068] The steps of manufacturing the upper coated glass body 200 include:
[0069] An upper electrode layer 202 is disposed on the lower surface of the upper glass substrate 201;
[0070] A second color-changing layer 203 is disposed on the lower surface of the upper electrode layer 202;
[0071] The upper glass substrate 201 , the upper electrode layer 202 and the second color-changing layer 203 are integrated into a whole by vacuum pressurization to obtain an upper coated glass body 200 .
[0072] At this time, the first color-changing layer 103 and the second color-changing layer 203 are connected to the same control source.
[0073] The preparation steps of the lower coated glass body 100 also include:
[0074] The lower glass substrate 101 is heated using a heating plate, and the temperature is set at 175° C.;
[0075] The lower electrode layer 102 is then evaporated onto the lower glass substrate 101, and then heated for a second time by an infrared heat lamp, the temperature is set to 350°C, and the pressure is set to 4mTorr using a vacuum device, and argon gas is used for secondary electric field acceleration, the flow rate of argon gas is set to 100sccm, the electric field voltage is set to 800V, and during the second pressurization, the infrared heat lamp is turned off, the second pressurization time is set to 2min, and then the pressure in the vacuum device is filled to 1mTorr to obtain the prepared part;
[0076] Heat the color-changing ink to 70°C and spray it on the workpiece by electrostatic spraying. The thickness of the color-changing ink spraying is 0.01mm. Then, nitrogen is introduced to blow away the excess powder. The volume flow rate of the introduced nitrogen is 0.3m 3 / h, and finally drying by hot air to obtain the lower coated glass body 100.
[0077] The upper coated glass body 200 is prepared by adopting the same steps.
[0078] Example 2
[0079] This embodiment provides a second method for preparing the lower coated glass body 100 and the upper coated glass body 200, referring to Figure 2 , specifically:
[0080] The steps of manufacturing the lower coated glass body 100 include:
[0081] A lower electrode layer 102 is disposed on the upper surface of the lower glass substrate 101;
[0082] A first color-changing layer 103 is disposed on the upper surface of the lower electrode layer 102;
[0083] The lower glass substrate 101 , the lower electrode layer 102 and the first color-changing layer 103 are integrated into a whole by vacuum pressurization to obtain a lower coated glass body 100 .
[0084] The steps of manufacturing the upper coated glass body 200 include:
[0085] An upper electrode layer 202 is disposed on the lower surface of the upper glass substrate 201;
[0086] The upper glass substrate 201 and the upper electrode layer 202 are integrated into a whole by vacuum pressurization to obtain an upper coated glass body 200 .
[0087] The preparation steps of the lower coated glass body 100 also include:
[0088] The lower glass substrate 101 is heated using a heating plate, and the temperature is set at 175° C.;
[0089] The lower electrode layer 102 is then evaporated onto the lower glass substrate 101, and then heated for a second time by an infrared heat lamp, the temperature is set to 350°C, and the pressure is set to 4mTorr using a vacuum device, and argon gas is used for secondary electric field acceleration, the flow rate of argon gas is set to 100sccm, the electric field voltage is set to 800V, and during the second pressurization, the infrared heat lamp is turned off, the second pressurization time is set to 2min, and then the pressure in the vacuum device is filled to 1mTorr to obtain the prepared part;
[0090] Heat the color-changing ink to 70°C and spray it on the workpiece by electrostatic spraying. The thickness of the color-changing ink spraying is 0.01mm. Then, nitrogen is introduced to blow away the excess powder. The volume flow rate of the introduced nitrogen is 0.3m 3 / h, and finally drying by hot air to obtain the lower coated glass body 100.
[0091] When the upper electrode layer 202 and the upper glass substrate 201 are integrated into a whole;
[0092] The upper glass substrate 201 is heated using a heating plate, and the temperature is set at 165° C.;
[0093] The upper electrode layer 202 is then evaporated onto the upper glass substrate 201, and then heated for a second time by an infrared heat lamp, the temperature is set to 200°C, and the pressure is set to 3mTorr using a vacuum device, and argon gas is used for secondary electric field acceleration, the argon gas flow rate is set to 100sccm, the electric field voltage is set to 800V, and during the second pressurization, the infrared heat lamp is turned off, the secondary pressurization time is set to 1min, and then the pressure in the vacuum device is filled to 1mTorr to obtain the upper coated glass body 200.
[0094] Example 3
[0095] According to Example 1, a lower coated glass body 100 and an upper coated glass body 200 are prepared.
[0096] This embodiment also provides a method for preparing LED color-changing laminated glass, which is specifically:
[0097] Add a film 300 between the lower coated glass body 100 and the upper coated glass body 200, put them into a vacuum bag, and evacuate them at a vacuum degree of 2.5 kPa for 15 minutes to obtain a pre-pressed product;
[0098] Then put the pre-pressed product into the autoclave, set the pressure to 1.3MPa, the duration to 30min, and the temperature to 135℃ to obtain the hot-pressed product;
[0099] The hot pressed product is then stored at 100°C for 2 hours, taken out and allowed to stand to cool, and then cut to size to obtain the finished product.
[0100] Example 4
[0101] According to Example 2, a lower coated glass body 100 and an upper coated glass body 200 are prepared.
[0102] This embodiment also provides a second method for preparing LED color-changing laminated glass, which is specifically:
[0103] Add a film 300 between the lower coated glass body 100 and the upper coated glass body 200, put them into a vacuum bag, and evacuate them at a vacuum degree of 2.5 kPa for 10 minutes to obtain a pre-pressed product;
[0104] Then put the pre-pressed product into the autoclave, set the pressure to 1.3MPa, the duration to 20-30min, the temperature to 100℃, and obtain the hot-pressed product;
[0105] The hot pressed product is then stored at 70°C for 2 hours, taken out and allowed to stand to cool, and then cut to size to obtain the finished product.
[0106] Example 5
[0107] This embodiment also provides steps for testing the finished product, specifically:
[0108] Before the finished product changes color: a light beam is emitted through the finished product, and the intensity is detected by a light beam detector at the other end of the finished product to obtain a first detection value;
[0109] After the finished product changes color: a light beam is emitted through the finished product, and the intensity is detected by a light beam detector at the other end of the finished product to obtain a second detection value;
[0110] The first detection value and the second detection value are analyzed to obtain a beam intensity score.
[0111] The calculation formula of the beam intensity score is:
[0112]
[0113] In the formula, G represents the beam intensity score, I1 and I2 represent the first detection value and the second detection value respectively, and α represents the determination factor, which is specifically 1 or 0.
[0114] In this embodiment, a laser source (such as a He-Ne laser) is prepared to emit a light beam through the photochromic glass; a light beam detector is prepared to measure the intensity of the light beam. The light beam detector can be a CCD camera or a photodetector to capture and measure the intensity distribution of the light beam;
[0115] Turn on the laser, emit a light beam through the finished product before color change, and record the first detection value I1 through the light beam detector at the other end. The image of the light intensity of the beam cross section can be captured by a CCD camera, and then the image is processed by computer software to display the light intensity curve;
[0116] Apply an electric field or other triggering conditions to the finished product to change it from a transparent state to a black state. After the color change is completed, a light beam of the same intensity is emitted again to pass through the color-changed glass. At the other end of the glass, a light beam detector is used to complete the detection of the light beam intensity, and the second detection value I2 is recorded. Finally, it is substituted into the calculation formula of the light beam intensity score to obtain the light beam intensity score;
[0117] Furthermore, the determination condition of the determination factor α is: when the intensities of the two emitted light beams are different, or other reasons lead to inequality in the implementation process, the output result of the determination factor α is 0, and the output result of the determination factor α is 1 in other cases.
[0118] The steps to test the quality of finished products also include:
[0119] Before the finished product changes color: set a color block image on one side of the finished product, and shoot with a camera on the other side of the finished product to obtain a first test image;
[0120] After the finished product changes color: set a color block image on one side of the finished product, and shoot with a camera on the other side of the finished product to obtain a second test image;
[0121] The first test image and the second test image are analyzed to obtain color intensity scores.
[0122] The calculation formula of the color strength score is:
[0123]
[0124] In the formula, Y represents the color intensity score, U1 and U2 represent the first analysis value and the second analysis value respectively, and β represents the determination factor, which is specifically 1 or 0.
[0125] In this embodiment, a color patch image, such as a standard 24-color patch image, is prepared for color analysis, a high-resolution camera is prepared for photographing the color patch image, and a computer and color analysis software (such as Imatest) are prepared for analyzing the photographed image;
[0126] Set a color block diagram on one side of the photochromic glass, ensure that the color block diagram is flat and evenly illuminated, use a camera to shoot on the other side of the glass to obtain the first test image, and ensure that the camera's white balance is set accurately and the exposure is appropriate to ensure true color restoration;
[0127] Apply an electric field or other triggering conditions to the photochromic glass to change it from transparent to black. After the color change is completed, use the camera to take a picture on the other side of the glass again to obtain the second test image. The first test image and the second test image are imported into the color analysis software. The software will automatically calculate the LAB value of each color block to obtain the first analysis value U1 and the second analysis value U2, which are substituted into the calculation formula of the color strength score to obtain the color strength score;
[0128] Furthermore, the determination condition of the determination factor β is: when the intensities of the two emitted light beams are different, or other reasons lead to inequality in the implementation process, the output result of the determination factor β is 0, and the output result of the determination factor β is 1 in other cases.
[0129] The beam intensity score and the color intensity score are combined to output a final score for the finished product. When the final score is greater than the threshold, the finished product is qualified.
[0130] The calculation formula of the final score is:
[0131]
[0132] In the formula, Z represents the final score.
[0133] In this embodiment, if the calculated color intensity score Y is 85%, the calculated beam intensity score G is 95%, and the final score Z is 90% through calculation, if the set threshold is 80%, the output result is that the finished product is qualified, and if the set threshold is 95%, the output result is that the finished product is unqualified.
[0134] Example 5
[0135] This embodiment also provides experimental data for finished product testing, as shown in Table 1;
[0136] Table 1: Test data of finished products with different structures
[0137] Example 3 Example 4 Comparative Example 1 Processing time 1.22h 1.05h 3h Preparation difficulty easy easy Disaster Beam intensity score 94% 96% 89% Color intensity score 97% 98% 90%
[0138] Comparative Example 1: Compared with Example 3 and Example 4, the film (300) is replaced with an electrolyte, and the preparation method adopts a method of pressing each layer one by one.
[0139] Processing time: 100 pieces of special-shaped glass are prepared, and Example 3, Example 4 and Comparative Example 1 are timed at the same time until 100 pieces of special-shaped glass are prepared.
[0140] Preparation difficulty: Since Examples 3 and 4 first complete the preparation of the finished product and then cut the glass into the required special-shaped glass, while Comparative Example 1 is a preparation step of pressing one by one, in order to ensure the safety of pressing, it is generally adopted to complete the cutting of the special-shaped glass first and then press the preparation. Therefore, since the size of the special-shaped glass is relatively strange, the subsequent preparation difficulty increases.
[0141] Light beam intensity score and color intensity score: The finished products of Example 3, Example 4 and Comparative Example 1 were tested respectively through the testing steps of Example 5 to obtain experimental data.
[0142] In summary, the present invention first presses the lower glass substrate, the lower electrode layer and the first color-changing layer into a whole, and then obtains the lower coated glass body and the upper coated glass body respectively in the same manner, and then manufactures the finished product, and cuts the prepared finished product according to actual needs. Compared with the existing method, this method does not need to consider the shapes of the lower glass substrate and the upper glass substrate, and can be directly prepared, thereby greatly improving the preparation efficiency.
[0143] After preparation is completed, through the inspection of the finished products, substandard products can be eliminated to ensure the pass rate of the entire batch. Secondly, the combination of the two sets of testing standards improves the testing efficiency, and they can form judgments with each other to ensure the authenticity of the test.
[0144] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A process for manufacturing LED color-changing laminated glass, characterized in that: include, Manufacturing a lower-layer coated glass body (100); Making an upper coating glass body (200); A film (300) is added between the lower coated glass body (100) and the upper coated glass body (200), and a lamination process is performed to obtain a finished product.
2. The process for manufacturing LED color-changing laminated glass according to claim 1, characterized in that: The manufacturing steps of the lower coated glass body (100) include: A lower electrode layer (102) is provided on the upper surface of the lower glass substrate (101); A first color-changing layer (103) is provided on the upper surface of the lower electrode layer (102); The lower glass substrate (101), the lower electrode layer (102) and the first color-changing layer (103) are integrated into a whole by vacuum pressurization to obtain a lower coated glass body (100).
3. The process for manufacturing LED color-changing laminated glass according to claim 2, characterized in that: The steps of manufacturing the upper coated glass body (200) include: An upper electrode layer (202) is provided on the lower surface of the upper glass substrate (201); A second color-changing layer (203) is provided on the lower surface of the upper electrode layer (202); The upper glass substrate (201), the upper electrode layer (202) and the second color-changing layer (203) are integrated into a whole by vacuum pressurization to obtain an upper coated glass body (200).
4. The process for manufacturing LED color-changing laminated glass according to claim 2, characterized in that: The steps of manufacturing the upper coated glass body (200) include: An upper electrode layer (202) is provided on the lower surface of the upper glass substrate (201); The upper glass substrate (201) and the upper electrode layer (202) are integrated into a whole by vacuum pressurization to obtain an upper coated glass body (200).
5. The process for manufacturing LED color-changing laminated glass according to claim 3 or 4, characterized in that: The preparation step of the lower coated glass body (100) further includes: The lower glass substrate (101) is heated using a heating plate, and the temperature is set at 175-185°C; The lower electrode layer (102) is then evaporated onto the lower glass substrate (101), and then heated for a second time by an infrared heat lamp, the temperature is set to 200-600°C, and the pressure is set to 4mTorr by using a vacuum device, and argon gas is used for secondary electric field acceleration, the flow rate of argon gas is set to 100-200sccm, and the electric field voltage is set to 800-1000V. During the second pressurization, the infrared heat lamp is turned off, the second pressurization time is set to 2 minutes, and then the pressure in the vacuum device is filled to 1mTorr to obtain the prepared part; Heat the color-changing ink to 60-90°C and spray it on the workpiece by electrostatic spraying. The thickness of the color-changing ink spraying is 0.007-0.03mm. Then, nitrogen is introduced to blow away the excess powder. The volume flow rate of the introduced nitrogen is 0.2m 3 -5m 3 / h, and finally drying by hot air to obtain the lower layer coated glass body (100).
6. The process for manufacturing LED color-changing laminated glass according to claim 4, characterized in that: When the upper electrode layer (202) and the upper glass substrate (201) are integrated into a whole; The upper glass substrate (201) is heated using a heating plate, and the temperature is set at 165-175°C; The upper electrode layer (202) is then evaporated onto the upper glass substrate (201), and then heated for a second time by an infrared heat lamp, the temperature is set to 200-550°C, and the pressure is set to 3-4mTorr using a vacuum device, and argon gas is used for secondary electric field acceleration, the flow rate of argon gas is set to 100-200sccm, the electric field voltage is set to 800-950V, and during the second pressurization, the infrared heat lamp is turned off, the second pressurization time is set to 1-2min, and the pressure in the vacuum device is filled to 1mTorr to obtain an upper coated glass body (200).
7. The process for manufacturing LED color-changing laminated glass according to claim 5, characterized in that: When preparing the finished product, the specific steps include: Adding a film (300) between the lower coated glass body (100) and the upper coated glass body (200), placing them in a vacuum bag, and evacuating the bag at a vacuum degree of 2.5 kPa for 10-15 minutes to obtain a pre-pressed product; Then put the pre-pressed product into the autoclave, set the pressure to 1.3MPa, the duration to 20-30min, the temperature to 100-135℃, and obtain the hot-pressed product; The hot pressed product is then stored at a temperature of 70-100°C for 2 hours, then taken out and allowed to stand to cool, and then cut to size to obtain the finished product.
8. The process for manufacturing LED color-changing laminated glass according to claim 7, characterized in that: After obtaining the finished product, the quality of the finished product is tested, wherein the testing step includes: Before the finished product changes color: a light beam is emitted through the finished product, and the intensity is detected by a light beam detector at the other end of the finished product to obtain a first detection value; After the finished product changes color: a light beam is emitted through the finished product, and the intensity is detected by a light beam detector at the other end of the finished product to obtain a second detection value; Analyze the first detection value and the second detection value to obtain a beam intensity score; The steps to test the quality of finished products also include: Before the finished product changes color: set a color block image on one side of the finished product, and shoot with a camera on the other side of the finished product to obtain a first test image; After the finished product changes color: set a color block image on one side of the finished product, and shoot with a camera on the other side of the finished product to obtain a second test image; Analyze the first test image and the second test image to obtain color strength scores; The beam intensity score and the color intensity score are combined to output a final score for the finished product. When the final score is greater than the threshold, the finished product is qualified.
9. The process for manufacturing LED color-changing laminated glass according to claim 8, characterized in that: The calculation formula of the beam intensity score is: Wherein, G represents the beam intensity score, I1 and I2 represent the first detection value and the second detection value respectively, and α represents the determination factor, which is specifically 1 or 0; The calculation formula of the color strength score is: In the formula, Y represents the color intensity score, U1 and U2 represent the first analysis value and the second analysis value respectively, and β represents the determination factor, which is specifically 1 or 0.
10. The process for manufacturing LED color-changing laminated glass according to claim 9, characterized in that: The calculation formula of the final score is: In the formula, Z represents the final score.